KEMAMPUAN HUKUM ISLAM DALAM MERESPON PROBLEMATIKA KONTEMPORER - Saidah, Saidah (DIKTUM: Jurnal Syariah dan Hukum, 2014)
The Islamic law derived by al-Qur’an and Hadis can give solution with the problems of muslim contemporary. The problem that apeear in prohibition of usury, eating pork and the obligation tover nakedness. This has been proved by the scientific of research so Islamic can give some respon the actual and comteporary issues. When the people know the damade, there is new effort not to do it. Therefore, one of alternative in Islamic law is implementation istinbath such qiyas, istihsan and maslahah mursalah to respon the actual issues. Abstrak: Hukum